Inovasi Pengembangan Ekosistem Bisnis Pedesaan Melalui Komoditas Jambu Kristal di Desa Cihideung Udik Kabupaten Bogor - Handian Purwawangsa; Slamet Susanto; Nandi Kosmaryadi; M. Wahyudin Nasrulloh M. Wahyudin Nasrulloh; Ainun Fiki (Institut Pertanian Bogor, 2025)
The village is the most real place where all economic and social activities of the community occur. From the village, all kinds of problems can be found along with the potential that can be developed. The existing potential needs to be developed so that the benefits can be felt by the surrounding community. Community service through the BIMA program in Cihideung Udik Village is carried out as an effort to encourage this potential. The service is carried out for 8 months from July to December 2024 with the aim of encouraging village progress by developing a rural business ecosystem through crystal guava commodities under the title of tourist villages. The scheme for developing a commodity-based business ecosystem is carried out in several stages starting from socialization, FGD, training, and intensive mentoring. Training and mentoring are key in completing the needs to form a village business ecosystem. The success indicators of the training and mentoring scheme are reflected in several aspects such as institutions, plant conditions, and community socialization. The institutional aspect gives good results with collaboration between institutions so that a tourist plan is born in Cihideung Udik Village. Meanwhile, the condition of the plants is considered good with a growth percentage reaching 100% and an average plant height reaching 60.84 cm. This shows that the training and mentoring scheme implemented is very effective so that it has a direct good impact on farmers. The development of this crystal guava commodity will help the economic growth of the local community and increase the tourist attractions in Cihideung Udik Village.